Journalism in the fight against fake news: a politicized framing - Felizardo Dos Santos, Silvia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The COVID-19 crisis has generated much information, not always truthful, which has caused an exponential increase in the spread of hoaxes and fake news with impacts on the participation of society in the guidelines for solving the health crisis, in addition to challenging public trust in the government and political parties. In this respect, the present study analyzes the posts about false news to coronavirus published by different Spanish media on their Facebook profiles, as well as their possible impacts on the disinformation combat and its contribution to democratic stability. The research analyzes 112 Facebook posts from five Spanish newspapers between January 30th and April 30th, 2020, and reveals politicization in informative processes.